2020
DOI: 10.1029/2019je006242
|View full text |Cite
|
Sign up to set email alerts
|

Space Weathering of FeS Induced via Pulsed Laser Irradiation

Abstract: Here we present results from pulsed laser irradiation of troilite samples in an effort to simulate space weathering on airless bodies via micrometeorite impacts. We find that the spectral trends observed in directly irradiated samples and samples with a vapor-deposited coating are different than those found in silicate minerals previously studied. For instance, direct laser irradiation causes our troilite samples to initially brighten, but continued irradiation causes darkening and a decrease in spectral slope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Troilite (FeS) and certain phases of graphitized carbon can show an absorption that is often centered at shorter wavelengths, as seen in panel B of Fig. 3 (Cloutis et al 1994(Cloutis et al , 2011aApplin et al 2018;Prince et al 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Troilite (FeS) and certain phases of graphitized carbon can show an absorption that is often centered at shorter wavelengths, as seen in panel B of Fig. 3 (Cloutis et al 1994(Cloutis et al , 2011aApplin et al 2018;Prince et al 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Changes in surface micro‐roughness and chemistry may both play a role in altering the optical reflectance, slope, and albedo of troilite and other minerals present on the surface of Psyche (Yon & Pieters, 1987 ). The size and relative abundance of troilite grains in the regolith as well as gardening rates and other concurrent sulfur‐depleting processes (e.g., Prince et al., 2020 ), will influence the detectability of weathering‐induced sulfur depletion by both instruments, while not being directly measured.…”
Section: Discussionmentioning
confidence: 99%
“…Other minerals have received less attention. Only a small number of studies have investigated space‐weathering effects on iron meteorites or their major mineral components (Bezaeva et al., 2015 ; Harries & Langenhorst, 2014 ; Loeffler et al., 2008 ; Matsumoto et al., 2020 , 2021 ; Prince et al., 2020 ; Wu et al., 2017 ). While there have been extensive engineering studies on the effect of the space environment on structural metals for spaceflight applications, these synthetic materials are poor analogs for iron meteorites due to their orders‐of‐magnitude smaller crystal sizes and differing microstructures, both resulting from the inability to synthetically crystallize materials over geologic timescales (Petrovic, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…4f). As for most recent studies, scientists either used troilite out from iron meteorites (Dibb et al., 2021) to have the most spectrally genuine elements or they purchased synthesized FeS powder (Prince et al., 2020). In the latter case, the FeS powder used in the study does not show the typical brownish‐gold appearance that is usually observed in genuine troilites (see this work Figs.…”
Section: Discussionmentioning
confidence: 99%